Colonic cancers fistulised to other segments of the digestive tube. Case series and review of literature. - Ali Kılıç (Archives of Clinical and Experimental Medicine, 2016)
BackgroundOccurrence of enteric fistulas caused by colon cancer is a rare. Preoperative diagnosis has some difficulty because of non-specific presentation and lack of appropriate combination of diagnostic techniques. MethodsFrom November 2008 to April 2012, patients with entero-enteric fistulas caused by colon cancer were reviewed with regard to demographic variables, clinical presentation, diagnostic evaluation, intra-operative findings, type of surgical procedure and pathologic examination.ResultsThere were four (3.92%) fistulas caused by colon cancer among 102 patients with adenocarcinoma of the colon. Fistulas were one colo-duodenal, one colo-gastric, one ceco-sigmoidal and one sigmoido-rectal in patients with a mean age 56.5 years. Presence of fistulas was not diagnosed preoperatively in any of the patients by using standard diagnostic techniques, i.e., endoscopy and computed tomography. Complete resection of tumor with tract of fistula was performed in all patients. Mean duration of follow-up period was 12.25 months, liver metastasis was detected in one patient, entero-cutaneous fistula in one.ConclusionsMalignant fistula formation caused by colon cancers is a rare event. Preoperative diagnosis could be achieved by using a combination of barium enema or meal and endoscopy. Surgical treatment via oncologic en bloc resection with negative microscopic margins is important for long-term survival.